Fighting rat menace in Sunway Metro - New Straits Times, Dawn Chan (2012)
AFTER making the rounds in 18 areas, the Subang Jaya Municipal Council carried out its rat eradication gotong-royong programme in the Sunway Metro commercial area for the first time on Saturday.